(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes information about the translations into Latin of about 40 works of scholars of antiquity and the medieval East, on social and humanitarian sciences, carried out in translation centers in Spain. Here, the information collected from sources and scientific literature devoted to the history of translations in Spain in the XII–XIII centuries is analyzed and classified.